Trade liberalization and manufacturing growth in Malaysia : a cointegration analysis / Karunagaran Madhavan, Deviga Vengedasalam and Veera Pandiyan Kaliani Sundram - Madhavan, Karunagaran; Vengedasalam, Deviga; Kaliani Sundram, Veera Pandiyan (Institute of Research, Development and Commercialization (IRDC), 2006)
This study examines the impact oftrade liberalization in the manufacturing sector in Malaysia. The theoretical framework for this study employs the Lucas model of "human capital model ofendogenous model". This study also uses the cointegration test and error correction techniques to measure the impact oftrade liberalization on Malaysian manufacturing sector during the period /963 - 2003. The empirical results ofcointegration test suggest that there exists a long run relationship between manufacturing output and its determinants of trade liberalization, labour, capital and education level. This study uses the error correction model (ECM) to determine the short-run dynamics around the equilibrium relationship and suggest that labour and trade liberalization have emerged as significant determinants for the manufacturing output in Malaysia.